Adsorption of Toxic Heavy Metal Methylmercury (MeHg) on Germanene in Aqueous Environment: A First-Principles Study - Muhammad Rifqi Al Fauzan; Trias Prima Satya; Galih Setyawan; Imam Fahrurrozi; Fitri Puspasari; Juliasih Partini; Sholihun Sholihun (Indonesian Journal of Chemistry, 2021)
We perform ﬁrst-principles calculations to investigate the adsorption process of methyl mercury (MeHg) on germanene with the presence of water molecules. We calculate the formation energy and density of states to determine the effect of the adsorption of MeHg on the structural and electronic properties of germanene. Our results show that MeHg is chemisorbed on germanene through a spontaneous reaction. The calculated formation energy of the system is -1.61 eV. We also carry out charge distribution and charge transfer calculations based on the Mulliken model to understand the adsorption mechanism of MeHg.